Dampak Pembelajaran Identitas Nasional Terhadap Perilaku Siswa Di Sekolah Dasar Melalui Pendidikan Kewarganegaraan - Riska Armianti; Oriza Elafani; Maylani Maylani; Nayla Sabil; Achmad Zidan Shalihin (TA'DIBAN, 2026)
In Citizenship Education (PKn) the role of learning national identity is the basis for forming the character of students in a country. This research aims to find out and understand the impact and role of national identity learning in shaping the character of elementary school students who have integrity and nationalism in an era of increasingly rapid globalization. National identity is a manifestation of cultural values that grow and develop in several aspects of life by having distinctive characteristics that can distinguish them from other nations.